COMPLIANCE GAINING DALAM PERSUASI KOMUNIKASI DAN KEBIJAKAN PUBLIK PEMERINTAH KOTA BUKITTINGGI TERKAIT PEMBANGUNAN PASAR ATAS - Melani Rahmadanty; Ernita Arif; Aidinil Zetra (Jurnal Ilmu Pemerintahan Widya Praja, 2019)
This study aims to see how the City Government of Bukittinggi applies compliance gaining strategies in persuading its people, when establishing public policies that have been decided regarding the development of the Pasar Atas. The five steps of the activities implemented, namely rewarding, punishing, expertise, personal commitments and impersonal commitments have been able to create the compliance of traders who are victims of Pasar Atas fires. This study uses a constructivist paradigm and a qualitative descriptive approach. Data collection is done by interview, observation, literature study and documentation. Based on the results of the research and data analysis, it was concluded that the rebuilding of the upper market which had previously been marred by massive demonstrations could be resolved properly. This happened because, the City Government of Bukittinggi had good communication persuasion in terms of conveying the public policies it took, both related to the rebuilding of the upper market and the temporary relocation of the shelter market. Community disappointment can be overcome at first, because they have a government that is very willing to accommodate the aspirations of its people and has a very good performance system. Because, basically public policies made by the government aim to regulate life together to achieve the agreed vision and mission, for the good and progress of the City of Bukittinggi.